-6+7(x-3)=37-x

Simple and best practice solution for -6+7(x-3)=37-x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6+7(x-3)=37-x equation:


Simplifying
-6 + 7(x + -3) = 37 + -1x

Reorder the terms:
-6 + 7(-3 + x) = 37 + -1x
-6 + (-3 * 7 + x * 7) = 37 + -1x
-6 + (-21 + 7x) = 37 + -1x

Combine like terms: -6 + -21 = -27
-27 + 7x = 37 + -1x

Solving
-27 + 7x = 37 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
-27 + 7x + x = 37 + -1x + x

Combine like terms: 7x + x = 8x
-27 + 8x = 37 + -1x + x

Combine like terms: -1x + x = 0
-27 + 8x = 37 + 0
-27 + 8x = 37

Add '27' to each side of the equation.
-27 + 27 + 8x = 37 + 27

Combine like terms: -27 + 27 = 0
0 + 8x = 37 + 27
8x = 37 + 27

Combine like terms: 37 + 27 = 64
8x = 64

Divide each side by '8'.
x = 8

Simplifying
x = 8

See similar equations:

| .08(x)+.12(x+250)=348 | | x+0.13x=3500 | | X^2-18x-31=0 | | 28=4/3w | | -7(-5k-8)=196 | | 24/0.3 | | 2f+3w=15.55 | | -272=3n-7(8n+1) | | 0.7z-3=0 | | 3.5+46.9*x-9.8*x^2=0 | | 6+3x=8+11 | | 1404=.02(x) | | 14M-28=4(M+3) | | 3y=28-4y | | X/3=x-31/2 | | (3x^5-2x^3+4)+(x^4+2x^3-7)= | | 2y-2/5=-1/3 | | 8(3a+6)=9(2a-3)-9 | | 5-(2x+4)=15 | | -8(-x-7)=-x+29 | | 24y-20x=72 | | 1404=.08(x)+.04(y) | | 4(x+1)=2(x+3)-4 | | Z^2=8+6i | | 11-w=187 | | 4x+1=3(x+2)+2x | | 20.44=1.5x*x | | 2n^2+3x-9=0 | | 20x-5y=1.2 | | 0=1.5x*x | | 2/3x-5=61 | | 672=.08(x) |

Equations solver categories